LOCATING THE BOUNDARY BETWEEN THE PLEISTOCENE AND THE HOLOCENE IN CHINESE LOESS USING LUMINESCENCE - Lai Zh.P.; Wintle A.G. (My University, 2006)
A detailed chronology has been obtained for a loess section at Yuanbao, situated at the northwestern edge of the Chinese Loess Plateau. The ages were obtained by the measurement of the optically stimulated luminescence (OSL) from coarse-silt-sized quartz grains. These ages showed that deposition at this site was continuous from 17 ka to the present, but that there was a decrease in the sedimentation rate from 0.60 to 0.10 m/ka at 13.489±1.15 ka, and this is proposed as the location of the Pleistocene/Holocene (P/H) boundary. A change in OSL sensitivity occurs at this depth. The depth and sharpness of this boundary is compared with the change obtained in low-field magnetic susceptibility (MS) measurements on 65 samples from the section. The MS changes gradually over 1.9 m and thus does not provide an easily discernible boundary. The new OSL-based sedimentation rates are used to calculate the mass accumulation rates for the Holocene and the end of the Pleistocene.
Keywords: CHINESE LOESS; PLEISTOCENE/HOLOCENE BOUNDARY; SEDIMENTATION RATE; LUMINESCENCE CHRONOLOGY; QUARTZ OSL; OPTICALLY STIMULATED LUMINESCENCE; MAGNETIC SUSCEPTIBILITY; Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен